Effects of Mixed Eucalyptus urophylla×E. grandis with Manglietia conifera and Michelia hedyosperma on Soil Nutrients and Enzyme Activities - Jun LIU; Chun MAO; Xiaomei HAN; Mei YANG (Guangdong nongye kexue, 2022)
【Objective】The study aimed to explore the changes of soil nutrients and enzyme activities under five afforestation models of Eucalyptus urophylla×E. grandis pure forest, Manglietia conifera pure forest, Michelia hedyosperma pure forest, Manglietia conifera×Eucalyptus urophylla×E. grandis and Michelia hedyosperma×Eucalyptus urophylla×E. grandis.【Method】Kjeldahl nitrogen analyzer was used to determine soil total N, NaCl extraction distillation method was used to determine soil available N, molybdenum antimony colorimetric method was used to determine soil total P, HCl-H2SO4 solution extraction method was used to determine soil available P, flame photometric method was used to determine soil total K and available K, potassium permanganate titration method was used to determine soil catalase activity, and dinitrosalicylic acid method, indophenol colorimetry and disodium phenylphosphate colorimetry were used to determine the activities of soil sucrase, urease and acid phosphatase, respectively.【Result】The contents of total N, total P, total K, available N, available P and available K in surface soil (0-20 cm) and the activities of sucrase, acid phosphatase, urease and catalase in surface soil were higher than those in deep soil (20-40 cm). In the surface soil (0-20 cm), the total N, available P, total K, catalase activity and urease activity of the soil were all the highest in mixed forest of Manglietia conifera×Eucalyptus urophylla×E. grandis, and the highest values were 0.50 g/kg, 4.99 mg/kg, 0.41 g/kg, 0.82 U/g·24h and 3.5 U/g·24h, respectively. The activities of available N, total P, available K, sucrase and acid phosphatase were all the highest in the mixed forest of Michelia hedyosperma×Eucalyptus urophylla×E. grandis, and the highest values were 62.97 mg/kg, 3.79 g/kg, 42.88 mg/kg, 60.14 U/g·24h and 1.50 U/g·24h, respectively. In deep soil (20-40 cm), the activities of available N, total P, total K and catalase were all the highest in the mixed forest of Manglietia conifera×Eucalyptus urophylla×E. grandis, and the highest values were 36.86 mg/kg, 1.94 g/kg, 0.29 g/kg and 0.74 U/g·24h, respectively, while the activities of total N, available P, available K, sucrase, urease and acid phosphatase were all the highest in the mixed forest of Michelia hedyosperma×Eucalyptus urophylla×E. grandis, and the highest values were 0.44 g/kg, 3.17 mg/kg, 23.35 mg/kg, 38.02 U/g·24h, 2.05 U/g·24h and 0.95U/g·24h, respectively.【Conclusion】The content of soil nutrient and activities of four enzymes of mixed Manglietia conifera×Eucalyptus urophylla×E. grandis were significantly higher than those of pure forest of Manglietia conifera and Eucalyptus urophylla×E. grandis, and the content of soil nutrient and activities of four enzymes of mixed Michelia hedyosperma×Eucalyptus urophylla×E. grandis were significantly higher than those of pure forest of Michelia hedyosperma and Eucalyptus urophylla×E. grandis, which indicated that the mixed forest of precious tree species and Eucalyptus urophylla×E. grandis was more conducive to enriching soil nutrients and improving soil enzyme activities.